2009
DOI: 10.1186/bcr2327
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXA1 and GATA-3 in breast cancer: the prognostic significance in hormone receptor-negative tumours

Abstract: Introduction The expression of additional genes, other than oestrogen receptor (ER), may be important to the hormoneresponsive phenotype of breast cancer. Microarray analyses have revealed that forkhead box A1 (FOXA1) and GATA binding protein 3 (GATA-3) are expressed in close association with ERα, both encoding for transcription factors with a potential involvement in the ERα-mediated action in breast cancer. The purpose of this study was to explore if the expression of FOXA1 and GATA-3 may provide an opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
143
4
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 38 publications
20
143
4
1
Order By: Relevance
“…GATA3 has also been reported to be coexpressed with another good prognosis indicator, FOXA1, in luminal A breast cancers and the expression of both proteins are known to predict for good prognosis (Ademuyiwa et al, 2010). There is also evidence that FOXA1 may also predict for better clinical outcome in ERa-negative breast tumours (Albergaria et al, 2009). GATA3 is also known to be required for specification and maintenance of the luminal phenotype in breast tissue (Kouros-Mehr et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…GATA3 has also been reported to be coexpressed with another good prognosis indicator, FOXA1, in luminal A breast cancers and the expression of both proteins are known to predict for good prognosis (Ademuyiwa et al, 2010). There is also evidence that FOXA1 may also predict for better clinical outcome in ERa-negative breast tumours (Albergaria et al, 2009). GATA3 is also known to be required for specification and maintenance of the luminal phenotype in breast tissue (Kouros-Mehr et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…4a). GATA3 is an important transcriptional regulator in both normal mammary gland development and breast cancer [39][40][41] , and low expression levels of GATA3 are associated with a poor prognosis 42 . Three genes, PTCH1, PPARA and NFIB, exhibit epistatic interactions with GATA3 and also display negatively correlated expression levels with GATA3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] Within the luminal, a subtype of IC, it has been shown that FOXA1 [10,11] and GATA-3 [22,24] can sub-classify patients into a low and high-risk groups based on their strong expression. FOXA1 via its actions on the p27 promoter, [16,17] is thought to maintain IC in a less proliferative state, with a decreased metastatic potential, [10][11][12][13] while GATA-3 is important in the maintenance of tumor differentiation and suppression of metastatic potential. [21] Therefore, it is not surprising that these transcription factors are highly expressed in DCIS as well, which by defi nition is an in situ (noninvasive) carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[21] GATA-3 genes are involved with induction of FOXA1 expression, with increased activity in ER(+) carcinoma; therefore, the highest expression of FOXA1 in IC should be seen in association with both GATA-3 and ERα expression, [27] which has been seen in IC. [12] However, this relationship has not yet been categorized in DCIS. The specifi c aim of this study is to analyze the expression for the fi rst time in DCIS of novel biological transcription markers FOXA1, GATA-3, along with established markers MIB-1 (Ki-67) and HER2-neu in ER(+) and ER(-) groups of DCIS.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation